POLISH VS. AMERICAN COURTROOM DISCOURSE: INQUISITORIAL AND ADVERSARIAL PROCEDURES OF WITNESS EXAMINATION IN PENAL TRIALS. WHAT COURT INTERPRETERS NEED TO KNOW ABOUT WITNESS EXAMINATION IN CRIMINAL TRIALS UNDER DISPARATE LEGAL SYSTEMS TO PROVIDE HIGH LEVEL INTEPRETING SERVICES IN THE LIGHT OF THE DIRECTIVE 2010/64/EU OF THE EUROPEAN PARLIAMENT AND OF THE COUNCIL OF 20 OCTOBER 2010? - BEDNAREK, Grażyna Anna (Comparative Legilinguistics, 2016)
The major objective of this paper is to redefine translational competence of court interpreters necessitated by the introduction of the Directive 2010/64/EU of the European Parliament and of the Council of 20 October 2010, which assures the right to translation and interpretation to the persons accused of committing a criminal offence and suspects, who do not understand the language of the investigative proceedings and court hearings so that they can exercise their right of defense, as well as the right to a fair trial. The implementation of the said Directive into the national law of each EU Member State seems to have outdated the definition of a competent court interpreter, who until the said Directive became effective on 13 October 2013, had mainly interpreted criminal trials within one legal system only and therefore was required to be fundamentally familiar with the procedures applied during the criminal trial within the legal system in which the criminal trial took place.